Udział różnych grup akcjonariuszy w nadzorze nad spółką akcyjną: The participation of various shareholder groups in corporate governance - Ignyś-Lipowiecka, Agnieszka (Management and Administration Journal, 2021)
This article focuses on the issue of participation of various shareholder groups in corporate governance. The groups discussed in the article include institutional investors, individual shareholders and the corporation’s employees. Both the ways in which those shareholders can influence the running of the corporation, and the benefits of such influence are presented